CRYRING@ESR: present status and future research. (26th November 2015) - Lestinsky, M; Bräuning-Demian, A; Danared, H; Engström, M; Enders, W; Fedotova, S; Franzke, B; Heinz, A; Herfurth, F; Källberg, A; Kester, O; Litvinov, Y; et al.
Abstract: The former storage ring CRYRING has been shipped from the Manne Siegbahn Laboratory in Stockholm to Darmstadt as a Swedish in-kind contribution to FAIR. At its new location downstream of ESR all ion species presently accessible in ESR can be transferred to CRYRING, in which ions with rigidities between 1.44 and 0.054 Tm can be stored. The original Swedish layout has been modified by reconfiguring the sequence of straight sections and by slightly increasing the circumference to ESR/2. Ions can be injected from ESR or from an independent 300 keV/u RFQ test injector. The instrumentation of the ring includes an RF drift tube system for acceleration and deceleration (1 T s −1, with a possibility for an upgrade to 7 T s −1 ), electron cooling, a free experimental section, and both fast and slow extraction of ions. We report on the present progress of this project, give a prospective timeline, and summarize the new research which will be enabled by this project. First beam for commissioning of the storage ring is expected for 2015, final bakeout to restore ultrahigh vacuum conditions in 2016 and ion beams injected through ESR in ∼2017.